1996
DOI: 10.1021/jo960316i
|View full text |Cite
|
Sign up to set email alerts
|

Exploratory Investigations Probing a Preparatively Versatile, Pyridinium Salt Photoelectrocyclization−Solvolytic Aziridine Ring Opening Sequence

Abstract: A novel pyridinium salt photoelectrocyclization-nucleophilic bicyclic aziridine ring opening reaction sequence has been investigated in order to determine its preparative potential. N-Alkylpyridinium perchlorates were found to undergo photoinduced electrocyclization upon irradiation in nucleophilic solvents, such as H(2)O and MeOH, to efficiently produce 6-alkyl-6-azabicyclo[3.1.0]hex-2-en-4-yl alcohols and ethers. The bicyclic aziridine photoproducts react with a number of different nucleophiles (e.g., H(2)O,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
60
0
2

Year Published

2001
2001
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 202 publications
(63 citation statements)
references
References 8 publications
1
60
0
2
Order By: Relevance
“…6-8. Some among them are extremely effective against such kind of diseases which influenced by nitrogen-activated protein kinase enzyme inhibitors. Some of them have antimicrobial activity , 11 cytotoxic effect against human cancer cells, 12 antiallergic activity, 13 central nervous system influencing activity, 14 antiproliferation activty. 15 Several derivatives are also widely used as agrochemicals, 16 antioxidant 17 and antiinflammatory agent.…”
Section: Introductionmentioning
confidence: 99%
“…6-8. Some among them are extremely effective against such kind of diseases which influenced by nitrogen-activated protein kinase enzyme inhibitors. Some of them have antimicrobial activity , 11 cytotoxic effect against human cancer cells, 12 antiallergic activity, 13 central nervous system influencing activity, 14 antiproliferation activty. 15 Several derivatives are also widely used as agrochemicals, 16 antioxidant 17 and antiinflammatory agent.…”
Section: Introductionmentioning
confidence: 99%
“…An elegant procedure for the conversion was reported wherein triphenylphosphine and tetrahaloalkanes were used [2]. Other notable synthetic procedures are the Mitsunobo reaction [3], the reaction of 2,4,6-trichloro- [1,3,5]-triazine (TCT) in DMF followed by addition of CH2Cl2 solution of the reactant alcohol [4], the reaction of alcohol with 2,3-trichloro-5,6-dicyanobenzo-quinone in the presence of triphenyl phosphine, CH2Cl2 and a phase transfer catalyst [5]. ROMP-gel supported triphenyl-phosphine [6], phosphorus(V) mediated nucleophilic substitution reaction [7] and finally the use of fluorous phosphine [8] besides others.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] Substituted pyrazolo [3,4-b]pyridines represent a very important building block in organic synthesis and numerous studies have been reported due to their well-documented biological activity. [5][6][7][8] Several 4-substituted pyrazolo [3,4-b]pyridines have been obtained by our group through nucleophilic substitution of the 4-chloro precursor with variable nucleophiles and showed antileishmanial, 5 antiviral 9 and antibacterial 10,11 promise. It is known that coupling molecules with well-established pharmacological activities might be a good strategy to develop new significant products.…”
Section: Introductionmentioning
confidence: 99%